1994
DOI: 10.1007/bf03015660
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic oral ephedrine reduces the incidence of hypotension after subarachnoid block

Abstract: Prophylactic oral ephedrine reduces the incidence of hypotension after subarachnoid block (1"3-1"4) and iv fluids, the total dose of ephedrine supplement in Group I was 4.3 + 4.8 mg compared with 11.6 + 9.4 mg in Group H (P < 0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Similarly, Sternlo et al [7] had investigated the efficacy of IM ephedrine in elderly patients undergoing hip arthroplasty under spinal anesthesia with plain bupivacaine and concluded that ephedrine administered in the paravertebral muscles immediately after spinal anesthesia was a simple and effective means of reducing the incidence of hypotensive episodes in the elderly patient. Katie et al [8] investigated two hundred women, ASA physical status I or II undergoing lower abdominal surgery concluded that oral ephedrine premedication (30 minutes before spinal anesthesia) was a simple and effective way of reducing the incidence of hypotension compared to control group (p<0.01). Kohki et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sternlo et al [7] had investigated the efficacy of IM ephedrine in elderly patients undergoing hip arthroplasty under spinal anesthesia with plain bupivacaine and concluded that ephedrine administered in the paravertebral muscles immediately after spinal anesthesia was a simple and effective means of reducing the incidence of hypotensive episodes in the elderly patient. Katie et al [8] investigated two hundred women, ASA physical status I or II undergoing lower abdominal surgery concluded that oral ephedrine premedication (30 minutes before spinal anesthesia) was a simple and effective way of reducing the incidence of hypotension compared to control group (p<0.01). Kohki et al…”
Section: Discussionmentioning
confidence: 99%
“…So, the prophylactic use of atropine helps in preventing the blunted reflexes thus increasing heart rate and cardiac output, which finally increases blood pressure. Various studies also showed that ephedrine too improve hemodynamic parameter when used preoperatively in spinal aesthesia [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of 50mg IM ephedrine was found to be associated with higher incidence of hypertension as shown in the study by Rout CC et al 11 and Rolbin SH et al 12 whereas the use of oral ephedrine either 30mg or 50mg was found to be associated with the no incidence of hypertension in study done by Kafle et al 2 and Eroglu et al 3 .…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Kafle and colleagues[14] demonstrated that oral ephedrine, given 30–45 min before surgery, is a simple and effective method of reducing the incidence of hypotension during spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 99%